European integration and the Feldstein-Horioka puzzle - Katsimē, Margarita 1966-; Gylfi Zoega 1963- (CESifo, 2015)
We estimate the Feldstein-Horioka equation for the period 1960 - 2012 and find structural breaks that coincide with the introduction of the European single market in 1993, the introduction of the euro in 1999 and the financial crisis in 2008. The results suggest that the correlation between investment and savings depends on institutions, exchange rate risk and credit risk. Furthermore, we find that the pattern of capital flows within the euro zone reflect differences in output per capita, the rate of growth of output per capita and budget balances.